Psychological Attributes and Socio-demographic Profile of the Victims of Suicidal Death - Sunny, Sonia Naznin; Simi, Tamanna Hossain; Hassan, S M Mainul; Zahan, Md Sarwar; Rahman, Md Jahidur; Tarafder, Aditi; Debnath, Milton Kumar (Community Based Medical Journal, 2026)
Suicide remains a pressing public health concern, with psychological and socio-demographic factors playing a critical role in its occurrence. In Bangladesh, where mental health resources are limited, understanding the profiles of completed suicide victims is essential for targeted prevention strategies. Despite increasing suicide rates, comprehensive local data on victim characteristics remain scarce. A retrospective, cross-sectional study was conducted in the Department of Forensic Medicine and Toxicology, Sir Salimullah Medical College, Dhaka, Bangladesh, from July 2023 to June 2024, to analyze the psychological attributes and socio-demographic profiles of completed suicide victims in Dhaka. Using purposive sampling, 137 completed suicide cases were analyzed based on autopsy reports, medical records, and family interviews. Our study that young adults aged 20-35 years accounted for 45% of cases, with males (58%) outnumbering females. Unmarried individuals (52%), the unemployed (35%), and low-income groups (60%) showed highest vulnerability. Psychological autopsies identified depression (40%), family conflicts (30%), and financial stress (25%) as predominant triggers. Hanging (50%) and pesticide poisoning (30%) emerged as the most frequent methods, reflecting the means of accessibility. A significant seasonal pattern (p=0.021) showed peak incidence during monsoon months (40%). This study identified that young, economically disadvantaged males with mental health concerns as Bangladesh's highest-risk suicide group. The findings underscore the urgent need for targeted prevention strategies combining mental healthcare, poverty alleviation, and means restriction to address this growing public health crisis. CBMJ 2026 January: vol. 15 no. 01 P:84-88